AI Tools’ Impact on ELT Learner Independence: Ethical Implications in Higher Education in Madhesh Province, Nepal - Dahal, Babu Ram; Paudel, Shiv Raj (Janajyoti Journal, 2025)
The integration of Artificial Intelligence (AI) into education is revolutionizing traditional teaching and learning practices, offering transformative potential in enhancing learner engagement and performance. In the field of English Language Teaching (ELT), AI tools are increasingly adopted to personalize instruction, improve accessibility, and foster learner autonomy. However, their use also raises significant ethical concerns, particularly regarding originality, critical thinking, and academic integrity. This study aims to explore the multifaceted impact of AI tools on ELT learners in higher education across Madhesh Province, Nepal. It focuses on identifying both the educational benefits and the ethical challenges associated with AI use in ELT contexts. A quantitative research design was employed, involving thirty purposively selected ELT learners and twenty English language teachers from various districts of Madhesh Province. Data were collected through structured questionnaires and analyzed to assess perceptions and experiences related to AI integration in ELT. The findings reveal a dual impact: while AI tools support learner autonomy, facilitate personalized learning, and enhance accessibility, they also contribute to increased plagiarism, reduced critical thinking, and suppressed creativity. The study concludes that although AI holds considerable promise for ELT, its implementation must be carefully balanced with ethical considerations to support holistic learner development.